NEUROPROTECTIVE POTENTIAL OF AZADIRACHTA INDICA LEAVES IN DIABETIC RATS - Gupta, Naveen Kumar; Srivastva, Nidhi; Puri, Sanjeev; BUBBER, PARVESH; Puri, Veena (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Azadirachta indica is a treasure of multiple pharmacological properties and presently leaves of this plant have been explored to evaluate the neuroprotective potential in diabetic rats. Methods: Male Sprague-DawleyÂ rats were injected with single intra peritoneal dose of streptozotocin (60mg/ Kg body weight (BW.) to develop animal model of diabetes. Post twenty one days of streptozotocin induction, animals were treated with aqueous Azadirachta indica Leaf Extract (ALE, 600mg/Kg BW.) for seven consecutive days. Followed this, all animals were evaluated for the levels of blood glucose, lipid peroxidation (LPO), C Reactive Proteins (CRP), pro oxidant biomarkers and histological changes. Results: Streptozotocin treated rats exhibited elevated levels of blood glucose, LPO, CRP and altered pro oxidant biomarkers in comparison to control rats. Additionally, histological alterations/damage was evidenced as fragmentation, vacuolization, inflammation etc. However, ALE treatment to these rats significantly decreased blood glucose levels, LPO, CRP levels and restored pro-oxidants status. Light microscopic and ultra microscopic analysis also indicated less damage, tissue architectural changes in comparison to untreated diabetic rats. Further decrease in hyperalgesia and inflammation levels; along with protective and restorative changes following ALE treatment suggested the neuroprotective potential of Azadirachta indica leaves in diabetic rats. Conclusion: The oral administration of ALE to streptozotocin induced diabetic animals resulted in neuro-protection against degenerative oxidative stress associated with metabolic and histopathological damage in the brain. Key words:Â Azadirachta indica, Antioxidants, Hyperalgesia, Neuroprotection Â Â